Comparison of in vitro and in vivo bioassays to measure thyroid hormone disrupting activity in water extracts. (January 2018) - Leusch, Frederic D.L.; Aneck-Hahn, Natalie H.; Cavanagh, Jo-Anne E.; Du Pasquier, David; Hamers, Timo; Hebert, Armelle; Neale, Peta A.; Scheurer, Marco; Simmons, Steven O.; Schriks, Merijn
Abstract: Environmental chemicals can induce thyroid disruption through a number of mechanisms including altered thyroid hormone biosynthesis and transport, as well as activation and inhibition of the thyroid receptor. In the current study six in vitro bioassays indicative of different mechanisms of thyroid disruption and one whole animal in vivo assay were applied to 9 model compounds and 4 different water samples (treated wastewater, surface water, drinking water and ultra-pure lab water; both unspiked and spiked with model compounds) to determine their ability to detect thyroid active compounds. Most assays correctly identified and quantified the model compounds as agonists or antagonists, with the reporter gene assays being the most sensitive. However, the reporter gene assays did not detect significant thyroid activity in any of the water samples, suggesting that activation or inhibition of the thyroid hormone receptor is not a relevant mode of action for thyroid endocrine disruptors in water. The thyroperoxidase (TPO) inhibition assay and transthyretin (TTR) displacement assay (FITC) detected activity in the surface water and treated wastewater samples, but more work is required to assess if this activity is a true measure of thyroid activity or matrix interference. The whole animal Xenopus Embryonic Thyroid Assay (XETA) detected some activity in the unspiked surface water and treated wastewater extracts, but not in unspiked drinking water, and appears to be a suitable assay to detect thyroid activity in environmental waters. Highlights: Thyroid activity of model compounds and water extracts tested in vitro and in vivo . Reporter gene assays sensitive to compounds, but unable to detect activity in water. Whole animal XETA assay most suitable to detect thyroid activity in water extracts.